Digital Communication Strategies in Tourism: The Impact of Reviewer and Influencer Content on Visit Decisions - Tanjung, Ratu Sinar Sari; Munajat, Mas Dadang Enjat; Novianti, Evi; Nugroho, Abiyoga Bimo (KOMUNIKA, 2024)
This study aims to explore the influence of review content on social media as an advertising medium on the decision of tourists to visit Tegal Mas Resort. This study focuses on the relationship between product and service quality and tourist satisfaction at Tegal Mas Lampung Resort Island. This study uses a quantitative approach with a survey method to collect data from social media reviews and tourist responses. Statistical analysis was used to test the relationship between Product Quality, Service Quality, and Tourist Satisfaction variables and their impact on visit decisions. The study’s findings show that Product Quality significantly influences tourist visit decisions, with a significance value of 0.000. These results show that positive reviews regarding product quality on social media contribute considerably to tourists' decisions to visit Tegal Mas Lampung Resort Island. The content of reviews on social media about Tegal Mas Lampung Resort Island significantly affects tourists’ decisions to visit. Therefore, using positive reviews on social media can be an effective strategy to attract visitors and increase tourist satisfaction.